2015
DOI: 10.1097/imi.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis Examining Differences in Short-Term Outcomes between Sutureless and Conventional Aortic Valve Prostheses

Abstract: Objective Sutureless aortic valve prostheses are anchored by radial force in a mechanism similar to that of transcatheter aortic valve implantation. Transcatheter aortic valve implantation is associated with an increased permanent pacemaker (PPM) requirement in a significant proportion of patients. We undertook a meta-analysis to examine the incidence of PPM insertion associated with sutureless compared with conventional surgical aortic valve replacement. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The reported incidence of pacemaker implantation ranges from 5.6 to 9.1% in the literature 19, 20 , worse than standard AVR (3.0%). Other significant complications include neurological events (transient ischemic attack or disabling stroke), myocardial infarction, kidney failure, and surgical site infections 21 .…”
Section: Sutureless Aortic Valve Replacement: Technique and Resultsmentioning
confidence: 99%
“…The reported incidence of pacemaker implantation ranges from 5.6 to 9.1% in the literature 19, 20 , worse than standard AVR (3.0%). Other significant complications include neurological events (transient ischemic attack or disabling stroke), myocardial infarction, kidney failure, and surgical site infections 21 .…”
Section: Sutureless Aortic Valve Replacement: Technique and Resultsmentioning
confidence: 99%
“…Ranucci et al reported that ACC time was an independent predictor of cardiovascular morbidity, and there was a 1.4% increase in relative risk in morbidity for every extra 1-minute cross-clamp time (5) . This relationship has been demonstrated recently, even in AVR surgery, which has shorter ACC times compared to other cardiac surgery operations (5) (6,7) .…”
Section: Discussionmentioning
confidence: 63%
“…Data published on the comparison between RD-AVR and SAVR underline the benefits of RD-AVR in terms of operative time reduction, CBP duration and increased effective orifice area and consequent lower postoperative transvalvular gradient [19] . The most common complications reported in the case of RD-AVR are higher incidence of pacemaker implantation, postoperative stroke and residual aortic regurgitation [20] , while the most common complications reported in the case of standard procedure tend to be exclusively surgery related as major bleeding or acute renal failure [21] . Totally in contrast to these previous studies, the German Aortic Valve Registry (GARY) recently analyzed a total of 22,062 patients who underwent isolated SAVR using SAVR or RD-AVR between 2011 and 2015 [22] .…”
Section: Discussionmentioning
confidence: 99%